A case report of primary cardiac capillary hemangioma. Issue 1 (2nd January 2016) - Fan, Jidan; Liao, Xiaobo; Zhou, Xinmin
ABSTRACT: Background: Hemangioma of the heart, presenting as a primary cardiac tumor is extremely rare. Methods: We present a 20-year-old male with a cardiac tumor which was incidentally discovered during routine clinical examination. Results: Echocardiography showed a large intramyocardial mass attached to the left ventricle, close to the apex. A tumor was shown near the apex of the left ventricle by Cardiac CT. We performed a total resection surgery of the tumor one week after admission and the patient recovered well and discharged from hospital 7 d after surgery. Conclusion: The pathological diagnosis was primary cardiac capillary hemangioma. No tumor recurrence was shown by echocardiography after 20 months follow-up visits.